Distribution of Diseases on F-18 FDG PET/CT at Armed Forces Institute of Radiology and Imaging, Rawalpindi - Jamal, Ali; Slehria, Atiq ur Rehman; Bilal, Rizwan; Baig, Ahmad Zafar; Shafique, Mobeen; Haleem, Aliya (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the spectrum of diseases on F-18 FDG PET/CT imaging at the Armed Forces Institute of Radiology and Imaging, Rawalpindi. Study Design: Cross-sectional study. Place and Duration of the Study: PET/CT and Cyclotron Department, Armed Forces Institute of Radiology and Imaging,Rawalpindi Pakistan, from Jul 2019 to Mar 2021. Methodology: The patients were scanned for staging, restaging, interim/response assessment and relapse/recurrence purposes. In addition, the frequency of various cancers and types of scans were determined. Scanning has been performe using GE Health care MiDR PET-CT Scanner. Results: A total of 1573 patients were included in the study. Male patients were 927(58.93%), and female patients were 646(41.06%). The most common diseases encountered were lymphoma 623(39.6%), breast cancer 193(12.2%), lung cancer 12(7.6%), colorectal cancer 88(5.5%) and unknown primary 84(5.3%). Amongst lymphoma, Non-Hodgkin’s lymphoma was the most common 276(44.3%), followed by Hodgkin’s lymphoma 267(42.8%). Conclusion: F-18 FDG PET/CT hybrid imaging is an important modality and can significantly alter patient management plans. Lymphomas were the most common disease in our spectrum, followed by cancers of the breast, lungs, colon-rectum and unknown primary cases, which can be managed well by PET/CT’s routine utilization.